THE GOAL OF SUCCESS IN DEVELOPING THAI HOME ECONOMICS FOR ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Chansamut, Artaphon (Universitas Negeri Yogyakarta, 2025)
Academic articles on the goal of success in developing Thai home economics for sustainable development goals are essential for a better life. Sustainable development is a complex and multifaceted concept, closely linked to various issues, particularly food, which serves as a key medium. Home economics, as an integrated science for improving quality of life, therefore plays a role in solving current problems using an integrated approach. The researcher discovered relevant articles based on the results of the literature review from both within and outside the country, found that the goal of success in developing Thai home economics for sustainable development goals emphasis is a strategy that aims to end poverty, Poverty, Zero Hunger, Global health and well-being, achieve gender equality and empowering all women and girls, while equipping people and communities with the knowledge and abilities to make decisions that will lead to a more sustainable future. This entails applying sustainability concepts to various home economics topics, including resource management, food systems, and community development.